Detection of human 11β-hydroxysteroid dehydrogenase isoforms using reverse-transcriptase-polymerase chain reaction and localization of the type 2 isoform to renal collecting ducts - Whorwood, C.B.; Mason, J.I.; Ricketts, M.L.; Howie, A.J.; Stewart, P.M. (Molecular and cellular endocrinology, 1995)
11β-Hydroxysteroid dehydrogenase (11β-HSD), responsible for the interconversion of hormonally active cortisol to inactive cortisone, dictates specificity for the mineralocorticoid receptor (MR) in the distal nephron and colon. Two isoforms of human 11β-HSD have been cloned, an NADP(H)-dependent (type 1) dehydrogenase/oxo-reductase enzyme, and a high-affinity NAD-dependent (type 2) unidirectional dehydrogenase. Using the reverse-transcriptase polymerase chain reaction (RT-PCR) amplification of RNA extracted from human adult tissues, type 1 11β-HSD mRNA was found in decidua, placenta, liver, lung, spleen, kidney medulla, cerebellum and pituitary, but was absent in kidney cortex, sigmoid and rectal colon, salivary gland and thyroid. In contrast, type 2 11β-HSD mRNA was found only in placenta and in the classical mineralocorticoid target tissues, kidney cortex, kidney medulla, sigmoid and rectal colon, salivary gland, and colonic epithelial cell lines (AAC1 and RGC28). In situ hybridization studies of renal cortex, cortico-medullary junction and medulla using a 35S-labeled antisense cRNA probe for type 2 human 11β-HSD, revealed specific localization of type 2 11β-HSD mRNA expression exclusively to renal cortical and medullary collecting ducts. Type 1 and type 2 isoforms of human 11β-HSD are expressed in a distinct tissue-specific fashion, in keeping with the proposed differences in their physiological roles. Type 2 11β-HSD is found predominantly in mineralocorticoid target tissues where it serves to protect the MR in an autocrine fashion.